2020
DOI: 10.1016/j.ophtha.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Primary Retinal Detachment Outcomes Study Report Number 2

Abstract: Purpose: Anatomically similar rhegmatogenous retinal detachments (RRDs) can be treated with scleral buckle (SB), pars plana vitrectomy (PPV), or SB combined with PPV (PPV/SB). This study compares moderately complex phakic primary RRD treated with SB, PPV, or PPV/SB to review anatomic and visual outcomes.Design: Multicenter, retrospective, interventional cohort study.Participants: Data were gathered on all patients from multiple retina practices in the United States with RRD in 2015 and >90 days of follow-up. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 20 publications
2
58
0
Order By: Relevance
“…Cataract development or progression is more prevalent in PPV, and PPV is associated with a slower visual recovery [22][23][24]. The average age of the patients in our study was 49:3 ± 18:9 years; six years after the surgery, A recent multicenter study also confirmed that patients with phakic moderately complex primary RRD who underwent scleral buckling had significantly better visual outcomes [10]. Several studies have reported that the use of chandelier-assisted scleral buckling yielded a reattachment rate of 83.3-95.5% [3,5].…”
Section: Discussionsupporting
confidence: 74%
“…Cataract development or progression is more prevalent in PPV, and PPV is associated with a slower visual recovery [22][23][24]. The average age of the patients in our study was 49:3 ± 18:9 years; six years after the surgery, A recent multicenter study also confirmed that patients with phakic moderately complex primary RRD who underwent scleral buckling had significantly better visual outcomes [10]. Several studies have reported that the use of chandelier-assisted scleral buckling yielded a reattachment rate of 83.3-95.5% [3,5].…”
Section: Discussionsupporting
confidence: 74%
“…Both delay in presentation and delay in surgical repair of macula-off retinal detachments are associated with worse visual acuity and surgical outcomes. 8 , 9 , 10 , 11 Prior studies have suggested a delay of 7 days can lead to worse visual outcomes, while some recent studies have suggested that a delay in even 3 days leads to worse visual acuity outcomes. 12 , 13 The purpose of this report is to investigate the effect of the initial COVID-19 pandemic on the clinical presentation of acute, primary RRD to a tertiary referral-based retina subspecialty practice setting.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent large multicenter study, scleral buckle showed better results (91.7%) than pars plana vitrectomy (83.1%) in moderately complex phakic primary RRD. 13 These results encourage surgeons to utilize this procedure in favorable contexts.…”
Section: Discussionmentioning
confidence: 92%